Relationship between interleukin-8 and the oxidant-antioxidant system in end-stage renal failure patients - (:unkn) unknown (BASKENT UNIV, 2007)
Objectives: We aimed to evaluate the relationship between interleukin-8 and the oxidant-antioxidant system in end-stage renal failure patients with and without diabetes mellitus undergoing regular hemodialysis treatment. Materials and Methods: Plasma levels of malondialdehyde and whole blood reduced glutathione were measured as markers of the oxidant and antioxidant systems, respectively. Plasma interleukin-8 levels were measured by enzyme-linked immunosorbent assay. Results: When compared with controls, plasma interleukin-8 levels were elevated in both diabetic and nondiabetic end-stage renal disease patients. Plasma malondialdehyde levels were statistically significantly higher in end-stage renal disease patients with and without diabetes mellitus than they were in controls; however, reduced glutathione levels were statistically significantly lower in diabetic and nondiabetic end-stage renal disease patients than they were controls. Conclusions: In end-stage renal disease patients with and without diabetes mellitus, elevated interleukin-8 levels and decreased reduced glutathione levels may be attributed to increased oxidative stress due to inflammation. In other words, increased reactive oxygen species may induce interleukin-8 production and result in diminished reduced glutathione levels. Our data suggest a relationship between interleukin-8 and the oxidant-antioxidant system in end-stage renal failure patients.
Keywords: cytokine; malondialdehyde; glutathione; NF-KAPPA-B; TRANSCRIPTION FACTORS AP-1; NECROSIS-FACTOR-ALPHA; EPITHELIAL-CELLS; DIFFERENTIAL ACTIVATION; OXIDATIVE STRESS; GLUTATHIONE; KIDNEY; INFLAMMATION; EXPRESSION